2015
DOI: 10.1556/650.2015.30132
|View full text |Cite
|
Sign up to set email alerts
|

Nem-konvencionális gyógymódok a háziorvos szemszögéből

Abstract: Bevezetés: A nem-konvencionális gyógymódokat a betegek igénye tartja fenn, és alkalmazásuk gyakran rejtve marad a családorvosuk előtt. Célkitűzés: Felmérni a családorvosok véleményét a nem-konvencionális gyógymódokról, oktatá-sukról és integrációjuk lehetőségeiről. Módszer: Önkéntes, anonim kérdőíves felmérés a Semmelweis Egyetem Család-orvosi Tanszékének két továbbképző rendezvényén. Eredmények: A 194 háziorvos (39,8%-os válaszadási arány) 14%-a rendelkezett természetgyógyász végzettséggel és egynegyedük alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As far as training opportunities in CAM methods are concerned, 55.8 % of healthcare professionals would like to learn about CAM according to a Swedish survey [35], while in England this number is 56 % [36]. In Hungary 56.7 % of family physicians would like to study CAM [37]. Our own findings reveal that 48.4 % of those surveyed would like to learn CAM: 32.5 % of surgeons and 56.0 % of anaesthesiologists, which is a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…As far as training opportunities in CAM methods are concerned, 55.8 % of healthcare professionals would like to learn about CAM according to a Swedish survey [35], while in England this number is 56 % [36]. In Hungary 56.7 % of family physicians would like to study CAM [37]. Our own findings reveal that 48.4 % of those surveyed would like to learn CAM: 32.5 % of surgeons and 56.0 % of anaesthesiologists, which is a significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a variety of studies conducted on whether patients inform their biomedical doctors concerning employed complementary or alternative treatments. Many authors found that patients generally do not disclose CAM use to their physician [ 36 , 37 ], but the opposite has also been documented, where all participants of the study readily informed their doctor about the topic [ 35 ]. Based on several studies, Faith reports that “reasons for lack of disclosure include concerns about negative reactions or judgment from providers, perceptions that CAM use is not something about which providers need to know, and providers not initiating discussions about CAM” [ 36 ].…”
Section: Biomedical Treatmentmentioning
confidence: 99%